Аспекти векторної задачі спряження на прикладі контактної задачі теорії пружності - Рибка, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
The vector conjugation problem for boundary values of piecewise holomorphic functions is solved without reducing it to separate scalar conjugation problems (in case of difficulty to do it), by applying the solutions of problems with fewer number of singular points.